Odpowiedź :
f) 3-10•x=9-4•x
3-10x=9-4x
-10x+4x=9-3 (przenoszenie ze zmienionym znakiem)
-6x=6 |:(-6)
X=-1
g) 5-2•x=9-6•x
5-2x=8-6x
-2x+6x=8-5
4x=3|:4
X= 0,75
D) -3+7•x-2=3•x-11+6•x
-3+7x-2=3x-11+6x
7x-3x-6x=-11+3+2
-2x=-6|:(-2)
x=3
3-10x=9-4x
-10x+4x=9-3 (przenoszenie ze zmienionym znakiem)
-6x=6 |:(-6)
X=-1
g) 5-2•x=9-6•x
5-2x=8-6x
-2x+6x=8-5
4x=3|:4
X= 0,75
D) -3+7•x-2=3•x-11+6•x
-3+7x-2=3x-11+6x
7x-3x-6x=-11+3+2
-2x=-6|:(-2)
x=3
Odpowiedź:
[tex]Poziom~~D\\d)\\\\-3+7\cdot x -2 = 3\cdot x -11 +6\cdot x\\\\-3+7x-2=3x-11+6x\\\\7x-5=9x-11\\\\7x-9x=-11+5\\\\-2x=-6~~\mid \div (-2)\\\\x=3\\\\Poziom ~~C\\\\f)\\\\3-10\cdot x =9-4\cdot x\\\\3-10x=9-4x\\\\-10x+4x=9-3\\\\-6x=6~~\mid \div (-6)\\\\x=-1\\\\g)\\\\5-2\cdot x = 9-6\cdot x\\\\5-2x=9-6x\\\\-2x+6x=9-5\\\\4x=4~~\mid \div 4\\\\x=1[/tex]